(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency and outcome of percutaneous Achilles tenotomy in the treatment of congenital clubfoot using the Ponseti method. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Orthopedic Department of Nishtar hospital, Multan from October 2022 to September 2023. Methods: All patients were assessed at the time of presentation and scoring was done by using Pirani scoring system. Ponseti method was used initially to treat clubfoot and cases of persistent equinus deformity were treated with Percutaneous Achilles tenotomy. SPSS version 23 was used for data analysis. Results: The total Pirani score, mid-foot contracture score and hind-foot contracture score of the patients was 4.21±1.25, 2.52±0.98 and 2.35±1.08, respectively. Percutaneous tenotomy was noted in61.2% patients. No association was found for percutaneous tenotomy with sex, age, Pirani score and laterality of deformity, (p>0.050). Conclusion: Achilles tenotomy is a safe and effective component of ponseti method of clubfoot treatment. Frequency of percutaneous Achilles tenotomy can be predicted by evaluating the Pirani scores at presentation. If the Pirani scores are low and the condition is detected early, the rate of percutaneous Achilles tenotomy is generally reduced.